If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -6 = -27 Reorder the terms: -6 + 3y = -27 Solving -6 + 3y = -27 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3y = -27 + 6 Combine like terms: -6 + 6 = 0 0 + 3y = -27 + 6 3y = -27 + 6 Combine like terms: -27 + 6 = -21 3y = -21 Divide each side by '3'. y = -7 Simplifying y = -7
| 3x-7=(x+4) | | 4x-4=-2 | | 7x-3=-5+6x-(4x+3) | | x^3-2=0 | | 10-8x=27-15x | | -x+11=5x+12-(7x-2) | | S^2-2s-8=0 | | 6x^2+4=10 | | 81-2(x-1)2=51 | | 3x^2-4=4-3x^2 | | -12x-9x=9x+24 | | 2x+5-15+3x=5 | | 6x(5x+3)=18x | | 5k-12=20 | | 2x+4(2x+4)=50 | | 8x-8=3x+4 | | 6x+80=9x-7 | | 12-7x=162-42x | | 129-9x=9x+15 | | 2*x*x+5=10 | | 9+.44444444444=19 | | 6x+83=9x-7 | | 2x^3-x^2-1=0 | | 2+45-3/2=12b | | 8t-5=19 | | 6x-11-7x+12= | | 4x^2-4x+4=0 | | -x^2+x-12=0 | | 4(y+3)=7-5y | | (19x-17)-(3x-72)=-13+(13x+83) | | 9-9x=84-44x | | (1x)(6x)+7x+12=0 |